The effect of aloe vera bioactive level as feed additive on the egg performances of laying hens - I.A.K Bintang; A.P Sinurat; T Purwadaria (Jurnal Ilmu Ternak dan Veteriner, 2005)
A study on the use of aloe vera bioactives as feed additive in layer ration was conducted. One hundred and twenty pullets strain Isa Brown were allocated into 5 treatments with 6 replicates and 4 birds/replicate. The treatments were: control,control+antibiotic (50 ppm zinc bacitracin), and control+ aloe vera at three levels (0.25; 0.50 and 1.00 g/kg). The treatments were conducted in a completely randomized design. Parameter measured were first initial body weight, age at 1st lay, feed intake, egg weight, hen day (%HD) and feed conversion ratio. The results showed that antibiotic and aloe vera used as additive for 9 months production did not significantly (P<0.05) affect all parameter measured, except feed intake of hens fed diet containing 0.5 g/kg aloe vera was significantly (P<0.05) higher than control. The addition of aloe vera at 1.0 g/kg significantly (P<0.05) reduced the feed intake as compared with the control, aloe vera 0.25 and 0.50 g/kg. The used of aloe vera (1.00 g/kg) produced egg weight significantly (P<0.05) higher than the control, and feed conversion ratio was significantly (P<0.05) better than the control and aloe vera (0.25 g/kg). It is concluded that the best treatment was the diet with aloe vera level at 1.00 g/kg. This treatment improved feed efficiency 8.40%.     Key Words: Bioactive, Egg Production, Layer